2009
DOI: 10.1510/icvts.2008.189431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and hemodynamic factors associated with the outcome of early extubation attempts after right heart bypass surgery

Abstract: Fast-track anesthesia with early extubation (EE) is playing an increasingly important role in pediatric cardiac surgery. We examined the pre- and intra-operative factors contributing to successful EE, and outcomes after right heart bypass surgery (RHB). We retrospectively reviewed the medical records of 71 consecutive children (median age=14 months) admitted over a 4-year period to the pediatric intensive care unit (PICU) of our university-based hospital, after RHB. We compared the characteristics and outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
3
19
1
Order By: Relevance
“…Kurihara et al retrospectively compared early extubated patients (<3 h) with late extubated ones (≥3 h) after BDG and TCPC; 54% patients were extubated early. [5] The early extubated patients had lower pre-operative mPAP, mean PVR and mean CVP whereas the late extubated patients (>3 h) had poor pre-and post-operative cardiac functions and higher PVR. Decreased cardiac functions, high PVR and the need for large doses of inotropes and vasodilators are the factors that can delay extubation.…”
Section: Regional Cerebral Tissue Oxygen Saturaɵonmentioning
confidence: 82%
See 4 more Smart Citations
“…Kurihara et al retrospectively compared early extubated patients (<3 h) with late extubated ones (≥3 h) after BDG and TCPC; 54% patients were extubated early. [5] The early extubated patients had lower pre-operative mPAP, mean PVR and mean CVP whereas the late extubated patients (>3 h) had poor pre-and post-operative cardiac functions and higher PVR. Decreased cardiac functions, high PVR and the need for large doses of inotropes and vasodilators are the factors that can delay extubation.…”
Section: Regional Cerebral Tissue Oxygen Saturaɵonmentioning
confidence: 82%
“…[3][4][5] Although these studies showed that reducing the duration of artificial ventilation by early extubation could minimize potential detrimental effects of positive pressure ventilation, [3][4][5] it is important to know the effect of different ventilation modes used during the weaning period after BDG and TCPC on organ perfusion. Walsh et al noted that ventilation with airway pressure (AWP) release ventilation improves pulmonary blood flow compared…”
Section: Original Articlementioning
confidence: 99%
See 3 more Smart Citations